2021
DOI: 10.1002/ab.22007
|View full text |Cite
|
Sign up to set email alerts
|

Injury patterns and associated demographics of intimate partner violence in men presenting to U.S. emergency departments

Abstract: Research suggests that there are differences between sexes in physical intimate partner violence (IPV) victimization that could lead to different injury patterns. In addition, research shows that men under‐report their injuries yet may suffer grave consequences. It is, thus, vital to establish physical injury patterns in male IPV victims. A retrospective review of prospectively collected data was performed using the National Electronic Injury Surveillance System‐All Injury Program data from 2005 to 2015 for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The 12 included studies reflect the varied composition of patients. With regard to participants' gender, 6 studies included women only, [18][19][20][21]23,29 5 studies included both women and men, 22,[24][25][26][27] and 1 study included men only. 28 In terms of medical populations of interest, three studies included a general population, 18,20,27 four studies involved only trauma patients, 22,[24][25][26] two studies involved only pregnant women, 23,29 and three studies involved highly specific populations with certain psychosocial attributes (two studies with HIV+ individuals who also either faced housing instability 19 or identified as gay or bisexual, 28 and one study involved women with substance use histories who were in intimate relationships with men involved in community corrections 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…The 12 included studies reflect the varied composition of patients. With regard to participants' gender, 6 studies included women only, [18][19][20][21]23,29 5 studies included both women and men, 22,[24][25][26][27] and 1 study included men only. 28 In terms of medical populations of interest, three studies included a general population, 18,20,27 four studies involved only trauma patients, 22,[24][25][26] two studies involved only pregnant women, 23,29 and three studies involved highly specific populations with certain psychosocial attributes (two studies with HIV+ individuals who also either faced housing instability 19 or identified as gay or bisexual, 28 and one study involved women with substance use histories who were in intimate relationships with men involved in community corrections 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…There seems to be a cumulative effect from IPV, meaning that the more often and serious the abuse is experienced during lifetime, the worse the health outcomes [6], illustrating the great potential of early identification. In the emergency department (ED), patients seek help for health problems that may be related to exposure to any form of intimate partner violence, but rarely to physical injuries [1,5]. IPV correlates with increased morbidity and mortality among men and women [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…As many as 54% of women seeking emergency care may have been exposed to IPV, but despite the number of patients exposed, only about 5% are identified by healthcare workers [15]. The number of men identified may be even lower [3,5]. These patients often have a complexity of emotional, physical and psychological distress.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations